The serum triglyceride to high-density lipoprotein (HDL) ratio in patients with acute coronary syndrome with and without renal dysfunction - Alen Džubur; Malik Ejubović; Almir Fajkić; Amela Dervišević; Azra Durak Nalbantić; Ajla Avdić Agić; Amela Džubur; Mevludin Mekić (Medicinski Glasnik, 2019)
Aim To assess triglyceride – to high-density lipoprotein cholesterol (TG/HDL)-C ratio in patients with acute coronary syndrome (ACS) and to verify its association with renal dysfunction. Methods A cross sectional study included 85 ACS patients divided in two groups with (ACS – RD) and without (ACS-nRD) presence of renal dysfunction, and 35 healthy subjects. Blood pressure, blood glucose, C-reactive protein, urea, creatinine, eGFR and serum lipids levels (total cholesterol, triglycerides, LDL-C, HDL-C) was measured in all participants. Based on the values of the measured lipid fractions TG/HDLc ratio was calculated. Results Patients in ACS group had significantly lower HDL-C level (p<0.0005) but significantly higher TG level (p=0.046) and TG/HDL-C ratio (p<0.0005) than controls. There was a significant increase (p<0.0005) in TG/HDL-C ratio in ACS-RD group compared to ACS-nRD group. The ACS-RD group had significantly higher level of TG (p=0.001), serum urea (p=0.02) and creatinine (p<0.0005) compared to the ACS-nRD group. With a cut-off level of 1.135 TG/HDL-C ratio had a sensitivity of 77.6% and a specificity of 62.9% in distinguishing between ACS patients and healthy subjects. With cut-off value of 1.905 TG/HDL-C ratio had a sensitivity of 75.9% and a specificity of 78.6% in distinguishing between ACS patients with and without renal dysfunction. Conclusion This study confirms the reliability of the TG/HDL-C ratio as a simple, low cost and useful marker in distinguishing between patients with ACS and healthy subjects and ACS patients with and without renal dysfunction.